The Influence Of Leadership Style On Employee Performance With Work Discipline As An Intervening Variable At PT. Bank Syariah Indonesia Kanca Palembang - Nuri Annisa Fitri; Hisbullah Basri; Firmansyah Arifin (UNIVED Press, 2025)
This study aims to determine the effect of leadership style on employee performance with work discipline as an intervening variable at PT. Bank Syariah Indonesia (Persero) Tbk. Palembang Branch Office. The data in this study are primary data in the form of questionnaires. Respondents in this study were employees at PT. Bank Syariah Indonesia (Persero) Tbk. Palembang Branch Office. The respondents of this study were 26 employees of PT. Bank Syariah Indonesia Kanca Palembang. This study uses two test methods, namely simple regression analysis and Path Analysis (Sobel Test). The results of the study show that leadership style has no effect on employee performance. Based on the calculated t value and significance value: it is known that the t value is 0.344 and the significance value is 0.734 > 0.05. That is, the first hypothesis is rejected. Furthermore, Leadership Style has no effect on Employee Performance with Work Discipline as an Intervening Variable. The results of the Sobel Test show that the a value is 0.073, the b value is 0.922, the Sa value is 0.213, the Sb value is 0.120. The value of the Statistical Test is 0.432 and the P-Value is 0.732. That is, the second hypothesis is rejected.